The CM/C Ratio Analysis of Virginian Tobbaco Ovening Business on Various Types of Fuel Use in East Lombok – Indonesia - Tajidan Tajidan; Rosi Septina Ningsih; IGL Parta Tanaya (Universitas Mataram, 2022)
The commonly used feasibility analysis formulas are R/C ratio, Gross B/C ratio and Net B/C ratio. In this analysis, we try to use the CM/C ratio analysis formula as an alternative to assess the feasibility of implementing a new technology. The purpose of this study was to assess the economic feasibility of using kerosene substitute fuel in the virgina tobacco oven process. To achieve the research objectives, data was collected using survey techniques on 44 tobacco farmers who have ovens in three sub-districts, namely Terara sub-district, Sakra sub-district and East Sakra sub-district. In each sub-district, one village was designated as the research location. The location of the research was determined by purposive sampling, which is the center of tobacco plants. Respondents in this study are farmers who have a Temakau Virginia oven in the research location selected by proportional accidental sampling technique as much as 20% of the population. The results showed that the use of kerosene, diesel, coal and liquefied gas fuels has been abandoned by farmers who work on oven ovens for viriginian tobacco, farmers have turned to palm shells, candlenut shells, and firewood. Almost half of the farmers who do tobacco ovens use firewood. The use of palm kernel shells, candlenut shells and firewood fulfills the requirements of economic feasibility with a CM/C ratio ranging from 24 percent to 65 percent higher than the bank interest rate of 4.5 percent per six months